Inhibiting renin angiotensin system in rate limiting step by aliskiren as a new approach for preventing indomethacin induced gastric ulcers. (25th October 2016) - Halici, Zekai; Polat, Beyzagul; Cadirci, Elif; Topcu, Atilla; Karakus, Emre; Kose, Duygu; Albayrak, Abdulmecit; Bayir, Yasin
Abstract: Purpose: Previously blocking the renin angiotensin system (RAAS) has been effective in the prevention of gastric damage. Therefore, the aim of this study was to investigate the effects of aliskiren, and thus, direct renin blockage, in indomethacin-induced gastric damage model. Methods: Effects of aliskiren were evaluated in indomethacin-induced gastric damage model on Albino Wistar rats. Effects of famotidine has been investigated as standard antiulcer agent. Stereological analyses for ulcer area determination, biochemical analyses for oxidative status determination and molecular analyses for tissue cytokine and cyclooxygenase determination were performed on stomach tissues. In addition, to clarify antiulcer effect mechanism of aliskiren pylorus ligation-induced gastric acid secretion model was applied on rats. Results: Aliskiren was able to inhibit indomethacin-induced ulcer formation. It also inhibited renin, and thus, decreased over-produced Angiotensin-II during ulcer formation. Aliskiren improved the oxidative status and cytokine profile of the stomach, which was most probably impaired by increased Angiotensin II concentration. Aliskiren also increased gastroprotective prostaglandin E2 concentration. Finally, aliskiren did not change the gastric acidity in pylorus ligation model. Conclusion: Aliskiren exerted its protective effects on stomach tissue by decreasing inflammatory cytokines and oxidative stress as a result of inhibiting the RAAS, at a rate-limiting step, as well as its end product, angiotensin II. Aliskiren also significantly increased protective factors such as PGE2, but not affect aggressive factors such as gastric acidity. Highlights: Aliskiren exerted protective effects against indomethacin induced gastric damage. Aliskiren reduced inflammatory cytokines and oxidative stress and increased PGE2. Aliskiren exerted these effects as a result of decreasing renin and angiotensin II.